Japanese contribution to Islamic studies: the legacy of Toshihiko Izutsu interpreted - Thoha, Anis Malik (IIUM Press, 2010)
This volume is a selection of papers and essays that have been improved thoroughly by their respective authors based on the discussion, comments, remarks, suggestions, criticisms etc. transpired at the sessions of the three-day-conference, i. e., the International Conference on Contemporary Scholarship on Islam: Japanese Contribution to Islamic Studies – The Legacy of Toshihiko Izutsu (ICONSIST), 2008, in Kuala Lumpur. It contains 19 essays covering different issues and topics relevant to Izutsu’s works, ranging from worldview (weltanschauung), philosophy, mysticism/sufism, semantics, linguistics and ethics to scientific study of religion. It includes also three articles in Arabic, which evidently show that the interest in Izutsu’s thought and works have gained a good deals of attention among the Arab scholars and readers as well.